Down-regulation of NF-κB signaling by Gordonia bronchialis prevents the activation of gut epithelial cells - Smaldini, Paola Lorena (2013)
The immunomodulatory power of heat-killed Gordonia bronchialis was studied on gut epithelial cells activated with pro-inflammatory stimuli (flagellin, TNF-α or IL-1β). Light emission of luciferase-transfected epithelial cells and mRNA expression of IL-1β, TNF-α, IL-6, CCL20, IL-8 and MCP-1 were measured. NF-κB activation was assessed by immunofluorescence and immunoblotting, and induction of reactive oxygen species (ROS) was evaluated. In vivo inhibitory properties of G. bronchialis were studied with ligated intestinal loop assay and in a mouse model of food allergy. G. bronchialis promoted the down-regulation of the expression of CCL20 and IL-1β on activated epithelial cells in a dose-dependent manner. A concomitant blocking of nuclear p65 translocation with increased production of ROS was found. In vivo experiments confirmed the inhibition of CCL20 expression and the suppression of IgE sensitization and hypersensitivity symptoms in the food allergy mouse model. In conclusion, heat-killed G. bronchialis inhibited the activation of NF-κB pathway in human epithelial cells, and suppressed the expression of CCL20. These results indicate that G. bronchialis may be used to modulate the initial steps of innate immune activation, which further suppress the allergic sensitization. This approach may be exploited as a therapy for intestinal inflammation.